Analisis Daya Motor Listrik DC dan Pompa Air DC pada Mesin Pengupas Kulit Singkong Tipe Silinder Abrasif - Azis Saputro; Ibrahim Lammada (Peneliti.net, 2023)
One of the methods of peeling on cassava is to use a cylinder with an abrasive layer that rotates on the cassava peeling machine.This research analyzes the electrical power needs in the operation of DC electric motors in the cassava peeling system and DC water pumps in the cassava washing system which is the constituent system of the cassava peeling machine that was developed. The research method used in this study is Research and Development. From the results and discussion, it is obtained if the amount of DC electric motor power value in the peeling process will be directly proportional to the weight of cassava, but the amount of DC water pump power value in the washing process is not directly proportional or inversely proportional to the weight of cassava. Then the amount of hourly power value of DC electric motors and DC water pumps will be directly proportional to the length of time span of the peeling and washing process carried out and directly proportional to the value of the electrical power used.